Development and validity testing of the Adolescent Health Literacy Questionnaire (AHLQ): Protocol for a mixed methods study within the Irish school setting. Issue 11 (11th November 2020) - Spillane, Ailbhe; Belton, Sarahjane; McDermott, Clare; Issartel, Johann; Osborne, Richard H; Elmer, Shandell; Murrin, Celine
Abstract : Introduction: Health literacy research has focused predominantly on the adult population, and much less is understood about this concept from an adolescent perspective. The tools currently available to measure adolescent health literacy have been adapted from adult versions. This limits their applicability to young people because of the developmental characteristics that impact on adolescents' behaviour, including impulse control and judgement skills. This protocol describes the intended development and validity testing of a questionnaire to measure health literacy in adolescents. Methods and analysis: This protocol describes this mixed methods study that has three phases: the first phase will involve grounded research with adolescents using qualitative group interviews, co-design and concept mapping workshops to understand what health and healthy behaviours mean to adolescents and to explore their health literacy needs and the potential domains for the questionnaire. The draft health literacy domains identified will be presented to the youth advisory panel, and the questionnaire will be altered based on their feedback. Cognitive pretesting of the questionnaire items will also be conducted. Phase 2 will involve piloting the questionnaire to a two-stage random sample of young people in five urban and rural schools in Ireland. Test–retest reliability will be conducted using Pearson correlation coefficient. Confirmatory factor analysis will also be conducted to analyse the psychometric properties of the questionnaire. Phase 3 will involve the questionnaire being rolled out to a nationally representative sample of adolescents (n=6052) in Ireland to assess their levels of health literacy. Ethics and dissemination: Ethical approval to conduct this study has been granted from the University College Dublin Human Research Ethics Committee – Sciences (LS-20–08). Informed assent from adolescents and informed consent from parents/guardians will be sought. The findings of this research will be disseminated at national and international conferences, as well as through publication in peer-reviewed journals.